The possibility of reducing the concentrations of some electrolytes (ammonium, nitrate, phosphate) from secondary treated wastewater using Filamentous green algae Mougeotia sp. (Latakia University Journal -Biological Sciences Series, 2021)
In this research, Mougeotia sp Isolet. From Sheikh Daher's fountain basin and its cultivation under appropriate cultivation conditions (temperature of 25 ± 2 ° C, brightness of 2500 lux, light shift 16 light / 8 dark) on Chu-10 solid and liquid culture medium.Use the filamentous green moss, Mougeotia sp. In advanced treatment of secondary treated wastewater taken from the treatment plant at Tishreen University under constant laboratory conditions (temperature of 25 ± 2 ° C, brightness of 2500 lux, light shift of 16 light / 8 dark), during the treatment the concentrations of electrolytes (ammonium-nitrate) were measured. Phosphates and chlorophyll-A concentrations every 3 days for 25 days.Accompany with the growth of the filamentous green moss, Mougeotia sp. An increase in the concentration of chlorophyll-a and a decrease in the concentrations of electrolytes, where the lowest concentration of ammonium was recorded at 14.33 mg / l, the rate of the rate of bio-removal rate was 22.48%, and the nitrate rate was recorded at 13.86 mg / l the lowest decrease, and the rate of the percentage of biological removal was 13.33%, and it recorded 5.22 mg / l the lowest decrease in the concentration of an anion. Phosphates, the rate of bio-removal rate was 23.84%.